Pengaruh Integritas dan Disiplin Kerja terhadap Kualitas Pelayanan di Kecamatan Jatinangor - Gilang , Riki; Zuarko Adji, Wilma (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The study aims to determine how influential integrity and work discipline are on the quality of service in Jatinangor sub-district. The author researched using quantitative methods. The population of this study is people in the Jatinangor area. The analysis techniques used are validity tests, reliability tests, t tests. Sample tests chosen by researchers are sampling as many as 40 respondents. The results of this study stated that there was a significant influence of integrity (X1) and work discipline (X2) on service quality (Y) in Jatinangor sub-district by 74.9%, while there were other factors that influenced 25.1%.